Two subtypes of symptomatic joint hypermobility: A descriptive study using latent class analysis - Di Mattia, F.; Fary, Robyn; Murray, K.; Howie, E.; Smith, Anne; Morris, Susan (BMJ Group, 2018)
Objective: To investigate a cohort of children with symptomatic joint hypermobility. Methods: Case notes for 318 children with joint hypermobility attending a rheumatology clinic were reviewed for clinical presentation, medical history, psychosocial factors and physical examination findings. Seven key variables were extracted and used as indicator variables in a latent class analysis to estimate the presence and number of subgroups of children with symptomatic joint hypermobility. Results: Two subgroups with differing clinical presentations were identified accounting for age and gender: an 'athletic-persistent' class (62%) characterised by higher probabilities for recurrent and chronic musculoskeletal pain, and less severe hypermobility; and a 'systemic-profound' class (38%) characterised by generalised hypermobility, recurrent musculoskeletal pain, gastro-oesophageal reflux and motor delay. Conclusion: Findings suggest the presence of two distinct presentations of children with hypermobility. This finding may be important for clinical decision-making and management of this group of children.